2019
DOI: 10.1007/s13181-019-00736-9
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology Investigators Consortium Case Registry-the 2018 Annual Report

Abstract: The Toxicology Investigators Consortium (ToxIC) Registry was established by the American College of Medical Toxicology (ACMT) in 2010. The Registry collects data from participating sites with the agreement that all bedside medical toxicology consultation will be entered. This tenth annual report summarizes the Registry's 2019 data and activity with its additional 7177 cases. Cases were identified for inclusion in this report by a query of the ToxIC database for any case entered from 1 January to 31 December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(74 citation statements)
references
References 14 publications
(35 reference statements)
5
58
0
Order By: Relevance
“…Tables 2 and 3 summarize selective demographics for age and gender and race and ethnicity, respectively. Gender breakdown was similar to recent years [2][3][4][5]. In 2020, 50.6% of cases involved female patients, and 1% involved transgender or gender non-conforming patients (37 female-to-male, 17 male-to-female, 8 gender non-conforming).…”
Section: Demographicssupporting
confidence: 65%
“…Tables 2 and 3 summarize selective demographics for age and gender and race and ethnicity, respectively. Gender breakdown was similar to recent years [2][3][4][5]. In 2020, 50.6% of cases involved female patients, and 1% involved transgender or gender non-conforming patients (37 female-to-male, 17 male-to-female, 8 gender non-conforming).…”
Section: Demographicssupporting
confidence: 65%
“…36 The Toxicology Investigators Consortium (ToxIC) Registry was established in 2010 by the American College of Medical Toxicology, and collects data on bedside medical toxicology consultations from 71 US-based and two non-US-based collaborating centres in 2018. 37,38 Although a specific pattern of acute harms is not available, the registry is able to provide an insight into the burden of presentations and associated medical toxicology consultations related to prescription medicine misuse/abuse. In the 2018 ToxIC Registry annual report, of the 7043 medical toxicology consultations undertaken in 2018, 3690 (52.4%) related to 'intentional exposure to a pharmaceutical' and of these consultations, 17.0% (627) were due to misuse/abuse of the pharmaceutical.…”
Section: Emergency Department Presentations and Hospital Datasetsmentioning
confidence: 99%
“…In the 2018 ToxIC Registry annual report, of the 7043 medical toxicology consultations undertaken in 2018, 3690 (52.4%) related to 'intentional exposure to a pharmaceutical' and of these consultations, 17.0% (627) were due to misuse/abuse of the pharmaceutical. 38 In an observational cohort study of 202 adolescents where a medical toxicology consultation was undertaken in relation to 'drug misuse' between January 2010 and June 2013, prescription medicines and over-the-counter medicines were the second and third most common drug groups reported [56 (27. One study from the ToxIC Registry reported on the pattern of acute tramadol toxicity in a series of 80 patients. Those patients who had 'misused' or 'abused' tramadol were more likely to develop seizures than those patients who had used tramadol for other reasons (odds ratio 3.2, 95% confidence intervals 1.2-8.3, p = 0.02).…”
Section: Emergency Department Presentations and Hospital Datasetsmentioning
confidence: 99%
See 2 more Smart Citations